Enthusiasm as the motor of history - Martínez Villarroya, Javier (Revista de Filosofía, 2023)
The “feeling of destiny” has marked history. However, the historiography of emotions has not devoted enough attention to it. In classical times it was considered for decision making. Later we find rich systematic reflections: Machiavelli, Montaigne, Smith, Tolstoy, Weber, Geertz, Adorno... After studying these testimonies, we analyze the case of Gandhi and his “inner voice”. Revitalizing the discussion about the feeling of destiny contributes to understanding phenomena such as populism. It is not possible to do politics only with reasons: emotions must be taken into account; among them, the enthusiasm.